Manajemen Strategis Organisasi Ombudsman RI untuk Optimalisasi Pengawasan Publik dan Pencegahan Maladministrasi Global - Pambudi, Andi Setyo; Riyanto, Rendy (Neolectura, 2025)
Maladministration and corruption remain major obstacles to achieving clean and sustainable governance. Abuse of authority, bureaucratic inefficiency, and weak public transparency have eroded public trust and exacerbated unequal resource distribution. The urgency of this study arises from the underutilized role of the Indonesian Ombudsman (Ombudsman Republik Indonesia/ORI) in international cooperation, despite its strategic potential in preventing cross-border maladministration. This study aims to analyze the role of ORI in preventing maladministration at both national and international levels and to identify institutional challenges and strengthening strategies. The research employs a qualitative approach with a descriptive-exploratory design, utilizing in-depth interviews with central and regional ORI officials, literature review, and thematic analysis of official documents, including ORI annual reports, the United Nations Convention against Corruption (UNCAC), and publications by Transparency International. The findings indicate that ORI has a strong legal foundation; however, limitations in cross-border regulatory frameworks, human resource capacity, and international recognition remain significant challenges. Policy recommendations include harmonizing national regulations with global standards, strengthening institutional capacity, enhancing international institutional diplomacy, and increasing political and public support to reinforce ORI’s role as a key actor in promoting transparent, accountable, and maladministration-free governance at the global level.